2005
DOI: 10.1080/17453670510041493
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area of the tendon and the muscle of the biceps brachii in shoulders with rotator cuff tears

Abstract: Background The intraarticular portion of the long head of the biceps tendon is often widened in shoulders with cuff tears. It is unclear whether this is a local phenomen or is caused by muscle hypertrophy.Methods We investigated morphological changes of the biceps brachii in 14 embalmed shoulders: 7 with intact rotator cuff and 7 with rotator cuff tears.We measured the cross-sectional area (CSA) of the tendon of the long head of the biceps (LHB) at 9 levels between the glenoid origin and the musculotendinous j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…Further cadaveric studies identified morphologic alterations (cross-sectional area widening) between biceps tendons from shoulders with normal and torn rotator cuffs. 31 Anterior shoulder pain with a rotator cuff tear is a relative indication for the removal of the proximal LHBB tendon from within the shoulder joint and bicipital groove with subsequent tenodesis or simple tenotomy.…”
mentioning
confidence: 99%
“…Further cadaveric studies identified morphologic alterations (cross-sectional area widening) between biceps tendons from shoulders with normal and torn rotator cuffs. 31 Anterior shoulder pain with a rotator cuff tear is a relative indication for the removal of the proximal LHBB tendon from within the shoulder joint and bicipital groove with subsequent tenodesis or simple tenotomy.…”
mentioning
confidence: 99%
“…The supratubercular ridge of Meyer and a prematurely shallow bicipital or intertubercular sulcus have been postulated to result in a variety of lesions after repetitive use or acute trauma. 18,20,21 These include acute or chronic peritendonitis, varying degrees of attrition or damage to the tendon, and subluxation or complete dislocation. 10 Another proposed cause of pathologic alterations of the tendon is its blood supply.…”
mentioning
confidence: 99%
“…The cross-sectional area of the LHB in cadaveric shoulders with rotator cuff tears was also significantly larger in both the intra-articular and extra-articular portions. 2,20 Although the mechanism of LHB disorders in relation to rotator cuff tears has not been fully elucidated, enlargement or flattening of the LHB has often been observed during rotator cuff surgery. This might be the result of compensation for inadequate cuff function.…”
Section: Discussionmentioning
confidence: 99%